Agreement of physical activity questionnaire with cardiorespiratory fitness - Maria Fatima Glaner (Universidade Federal de Santa Catarina, 2007)
Many health benefi ts are associated with physical activity level (PAL), but no standardized approaches to measurement exist, and comparisons and surveillance are problematic. The aim of this study was to verify the level ofagreement between the results of the International Physical Activity Questionnaire (IPAQ: short) and the Habitual Physical Activity Questionnaire (HPAQ) with true cardiorespiratory fi tness (VO2max), in order to classify young men and women ashaving PAL that is either adequate or inadequate for good health. A convenience sample was studied, composed of 105 young adults (43 male physical education students; 28 female physical education students; 34 males not studying physicaleducation). Both questionnaires were self-administered under the identical conditions. Values for VO2max were obtained using Cooper's 12 min running test. Subjects were classifi ed as having PAL and VO2max that were adequate or inadequatefor good health. The cut off points used to defi ne adequate VO2max ≥44 ml/kg/min-1 for men and ≥33 ml/kg/min-1 for women. Agreement was assessed using a 2x2 contingency table. Percentage agreement ranged from 51.10% to 64.70% for theHPAQ and was 47.06% for the IPAQ. Agreement was higher for the HPAQ than for the IPAQ. Women overestimated their PAL by HPAQ and men underestimated their PAL by both questionnaires. The fi ndings of this study suggest that the HPAQ tends to be more accurate than the IPAQ. RESUMOMuitos benefícios à saúde são associados ao nível de atividade física (NAF), mas não existem medidas padronizadas para tal e, comparações e monitorações são difíceis. O propósito deste estudo foi verifi car a concordância do Questionário Internacional para Atividades Físicas (IPAQ - curto) e do Questionário de Atividades Físicas Habituais (QAFH) com a aptidão cardiorrespiratória (VO2max), para classifi car homens e mulheres jovens, com níveis de atividade física (NAF) recomendado, ou não, para a saúde. A amostra foi de conveniência composta por 105 adultos jovens (n= 34 homens; n=43 homens estudantes de Educação Física (EEF); n= 28 mulheres EFF). Os questionários foram auto-administrados nas mesmas condições. O VO2max foi obtido pelo teste de Cooper (corrida de 12 min). Os sujeitos foram classifi cados com NAF e VO2max recomendados, ou não, para a saúde. Para classifi car aqueles sujeitos com VO2max recomendado, os pontos de corte foram ≥44 ml/kg/min-1 (homens) e ≥33 ml/kg/min-1 (mulheres). A concordância foi acessada, usando uma tabela de contingência (2x2). O percentual de concordância oscilou de 51,10% a 64,70% para o QAFH e foi de 47,06% para o IPAQ. A concordância foi maior para o QAFH do que para o IPAQ. As mulheres tiveram seu NAF superestimado pelo QAFH e, os homens tiveram seu NAF subestimado pelos dois questionários. Os resultados deste estudo sugerem que o QAFH tende a ser mais acurado do que o IPAQ.